2017
DOI: 10.1071/an15458
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses on bodyweight, reproductive, and carcass traits in composite beef cattle

Abstract: In beef cattle, growth, reproductive, and carcass traits have been studied for improving productivity and quality of meat products. The aim of this study was to estimate genetic parameters for birth (BW), weaning (WW) and yearling (YW) weights, scrotal circumferences at weaning (SCW) and yearling (SCY), age at first calving (AFC), ribeye area (REA) and back fat thickness (BFT) in order to provide support for the evaluation program of the composite Canchim breed. Data on 12 967 (BW), 7481 (WW), 5131 (YW), 1447 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
6
16
1
9
Order By: Relevance
“…For W210, the direct heritability estimates were in agreement with those obtained by Zuin et al (2012), Bernardes et al (2015), and Pires et al (2016) for the Nelore, Tabapuã, and Canchim breeds. Lopes et al (2016), Vargas et al (2014), and Mota et al (2013) observed h 2 d for W450 in Nelore, Brahman, and Simmental animals of 0.52 ± 0.02, 0.22 ± 0.06, and 0.27, respectively.…”
Section: Resultssupporting
confidence: 82%
“…For W210, the direct heritability estimates were in agreement with those obtained by Zuin et al (2012), Bernardes et al (2015), and Pires et al (2016) for the Nelore, Tabapuã, and Canchim breeds. Lopes et al (2016), Vargas et al (2014), and Mota et al (2013) observed h 2 d for W450 in Nelore, Brahman, and Simmental animals of 0.52 ± 0.02, 0.22 ± 0.06, and 0.27, respectively.…”
Section: Resultssupporting
confidence: 82%
“…The heritability estimates are consistent with the values reported in the literature for subcutaneous fat thickness of both B. taurus (Schenkel et al, 2004;Pires et al, 2017) and B. indicus (Santana et al, 2014), as well as for scrotal circumference (Schenkel et al, 2004;Silva et al, 2013;Pires et al, 2017). However, the heritability for days to calving obtained in the present study was higher than that reported for B. taurus (Mu et al, 2016) and B. indicus (Forni and Albuquerque, 2005), whereas the heritability for RFI was lower than either B. taurus (Mu et al, 2016) or B. indicus (Santana et al, 2014).…”
Section: Genetic Evaluationsupporting
confidence: 91%
“…The genetic correlations between subcutaneous fat thickness and male and female fertility were of low magnitude but consistent in terms of signaling genetic synergism, that is, selection for greater fat thickness could have a tendency to increase the animal's breeding value for greater fertility. Low synergistic genetic correlations between fat thickness and scrotal circumference have also been reported in other studies (Schenkel et al, 2004;Yokoo et al, 2010;Pires et al, 2017). Similarly, low synergistic genetic correlations were found between fat thickness (or body condition score) and age at first calving (Caetano et al, 2013) or days to calving (Mercadante et al, 2006;Laurence et al, 2016).…”
Section: Genetic Evaluationsupporting
confidence: 58%
“…Direct and maternal heritability estimates for scrotal circumference at weaning obtained by Pires et al [22] were equal to 0.32 AE 0.06 and 0.06 AE 0.02, respectively, in Canchim beef cattle. For scrotal circumference at yearling age, these authors found direct heritability estimate of 0.49 AE 0.08.…”
Section: Traitsmentioning
confidence: 76%